Thigh phlegmon as a first sign of a ruptured pelvic presacral abscess caused by ileal diverticulum fistula: A case report. (April 2021) - Simcikas, Dainius; Maksimova-Cesnaviciene, Alisa; Gvazdaitis, Mindaugas; Jurgaitis, Jonas; Cizauskaite, Agne; Samalavicius, Narimantas Evaldas
Highlights: Ileal diverticulum rarely causes pelvic abscess. Pelvic abscess rarely causes thigh phlegmon. Rupture of presacral abscess to extra-pelvic site carries high mortality. Intrapelvic pathology has to be considered in patients with thigh phlegmon. Abstract: Introduction: Ileal diverticula usually remain asymptomatic. If complicated, they may present as intra-abdominal or pelvic abscess. Abscess formation in the presacral space is very rare. The rupture of abscess and spread of pus to extra-pelvic sites through anatomical structures of the pelvis is extremely rare. It carries high mortality if not diagnosed on time. Case presentation: We report a case of 52-year-old woman presented with thigh phlegmon and septic condition. The CT scan revealed free air in the left leg and pelvic presacral fluid collection descending to extra-pelvic direction through the greater sciatic notch. Moreover, ileal fistula to presacral abscess was suspected. Multiple incisions and fasciotomies were urgently performed to treat thigh phlegmon. Subsequently, laparotomy was carried out and ileal fistula was excised. Histological examination of the surgical specimen demonstrated that the fistula to presacral abscess has formed due to perforated ileal diverticulum. 3 years after the surgery the patient remains healthy without recurrence. Discussion: Rupture of presacral abscess to extra-pelvic site due to ileal diverticulum fistula is an extremely rare case, to our best knowledge, never reported in literature. Due to a rare occurrence and early septic complications if diagnosed late, this condition carries a high mortality rate. Conclusion: Intrapelvic pathology must be considered in patients with thigh phlegmon in order to prevent complications and associated mortality.